Reformasi Sistem Peradilan Pidana Indonesia: Tantangan dan Solusi Menuju Keadilan Efektif - Cyta Sucy Marrismawati; Arini Asriyani; Muhammad Rusdi; Suprapto Suprapto; Sul Hendrawan (Jurnal Litigasi Amsir, 2024)
The criminal justice system in Indonesia has undergone significant reforms to improve independence, capability, and responsiveness to human rights, with important regulations such as the Criminal Procedure Code, the Juvenile Criminal Justice System Law, and the Correctional System Law. However, major challenges still exist related to funding, operational competence, and coordination between law enforcement agencies. Suboptimal implementation, especially in the implementation of restorative justice and the protection of victims' rights, indicates the need for a systemic and comprehensive approach. Capacity building of law enforcement officials and inter-agency cooperation are needed to ensure a more effective and fair criminal justice system, so as to provide better justice for all parties involved.